Comparison of Three Different Fertigation Strategies for Drip Irrigated Table Grapes - Part I. Soil Water Status, Root System Characteristics and Plant Water Status - Myburgh, P.A.; Howell, C.L. (South African Journal of Enology and Viticulture, 2016)
Three fertigation strategies were compared in a drip irrigated Dan-ben-Hannah/Ramsey vineyard near Paarl in the Berg River Valley region of South Africa during the 2002/03 and 2003/04 seasons. Fertilisers were applied either (i) three times per season, (ii) once a week from bud break to flowering, from fruit set to véraison and for six weeks after harvest or (iii) in five to seven pulses per day. For each of the fertigation strategies, grapevines bore normal or high crop loads, viz. 26 or 36 bunches per grapevine respectively. Daily irrigation pulses of 20 to 40 minutes each maintained soil water matric potential above -0.01 MPa in the wetted bulbs. Daily pulses accumulated to a seasonal total of ca. 490 mm irrigation compared to ca. 260 mm for weekly irrigation. Root structures of grapevines irrigated by means of daily pulses had adapted by forming extremely dense root systems in the small wetted bulbs compared to the less frequently irrigated grapevines. Monitoring diurnal grapevine water status revealed that the different fertigation strategies did not affect water constraints up to véraison. During berry ripening, daily pulse irrigated grapevines experienced less water constraints in the morning, late afternoon and during the night than less frequently irrigated ones. However, the grapevines did not experience any detrimental water constraints throughout the season, irrespective of fertigation and irrigation frequencies or crop load. It was evident that grapevine water status not only depends on the size of the root structure, but also on the soil environment in which the roots function.